Diseño De Un Plan De Manejo Ambiental Para La Planta De Producción De Materiales Pétreos, Hormigón Y Asfalto La Josefina, Cantón Gualaceo, Provincia Del Azuay - Vásconez, Norma Ximena Lara; Arias, Oscar Bladimiro Guadalupe; Guamán, Juan Pablo; Salazar, Eduardo (European Scientific Journal, ESJ, 2017)
This research was to propose the elaborate of a Design Plan for Environmental Management Production Plant Stone Materials, Concrete and Asphalt in Josefina town, Gualaceo city, in Azuay province; it based on the collection of both primary and secondary, in addition to characteristics of the environment and population of area influence proceeded to design environmental management plan, these programs the same which is composed of nine programs intended to prevent or mitigate environmental impacts caused by the operation of the same, are: Communication Program, Community Relations, Training and Environmental Education, discharges and Waste Management, Safety and Occupational Health Laboring, contingencies, Prevention and Control of Impacts, Closure and Abandonment, Environmental Monitoring and Security. This research conclude that the most affected components are soil, water, flora and fauna and it is essential to fully comply all programs previously proposed in order to mitigate environmental impacts cauded by the operation of the Production Plant Stone Materials, Concrete and Asphalt. It is recommended to train staff, especially in first aid and use PPE (Personal Protective Equipment) so they will be prepared for any eventuality to occur during the operation of the plant.